Dampak Transformasi Tenaga Kerja Petani Ke Sektor Non- Pertanian Terhadap Kesejahteraan Rumah Tangga di Kabupaten Aceh Barat dan Kabupaten Aceh Selatan - Ariani, Nia; Noviar, Helmi; Ertika, Yenny (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Still today, Indonesia's agricultural industry provides the bulk of the country's GDP. Agricultural output and job prospects are deteriorating as a result of the COVID-19 pandemic, which is particularly severe from 2020 to 2022. These underlying causes highlight the need of having a framework to estimate and anticipate output for the next year. The objective is to examine how the transition of farm and non-agricultural labour has affected family welfare in the districts of West Aceh and South Aceh. Shift Share and Location Quotient (LQ) are the tools used in this study. Using the contribution criterion in particular, LQ analysis is a powerful analytical technique for revealing an area's economic foundation. One way to look at regional economic development is via shift share analysis, which tracks how a key indicator of regional economic growth changes or increases over a certain time period. Agriculture, forestry, and fisheries make up the basic sector in South Aceh Regency's LQ calculation. The manufacturing industry, construction, financial and insurance services, and government administration, defence, and compulsory social security make up the other three subsectors. Agriculture, forestry, and fishing make up the backbone of West Aceh Regency's LQ calculation. The quarrying and mining industry. All sectors in South Aceh Regency had a negative value in the GRDP of South Aceh Regency shift share study, which suggests that overall, the sectors in South Aceh Regency are not expanding faster than their counterparts in Aceh Province and West Aceh Regency. All of the sectors in West Aceh Regency's GDRP are positive, which indicates that overall, the South Regency's sectors are developing at a quicker rate than both Aceh Province and South Aceh Regency's sectors.